Rohu Generation 3 Dissemination: Bangladesh impact assessment - Dam Lam, Rodolfo; Yeasin, Mohammed; Hamilton, Matthew (WorldFish, 2024)
The dissemination of G3 rohu through a robust network of hatcheries and nurseries across Bangladesh marked a key milestone in this improvement program. By 2022, spawns from the G3 line had been propagated across multiple hatcheries. The hatcheries have subsequently grown this spawn into broodstock and commenced the production and sale of the genetically improved rohu seed in mid-2022 to nurseries with the objective of reaching end-users by 2023. WorldFish track the dissemination of 48 of these nurseries (24 offering non-G3 rohu and 24 offering G3 rohu) from two Divisions (Khulna and Rajshahi). The nurseries have started to disseminate these G3 rohu to final customers starting from the last quarter of 2022 and throughout the first half of 2023. This study follows up on the adoption and performance of the G3 rohu strain in these areas, assessing its socio-economic impact on producers, farmers, and consumers within Bangladesh's aquaculture industry.